STRATEGI PENGEMBANGAN KAWASAN WISATA BERBASIS KOMUNITAS (COMMUNITY BASED TOURISM) DALAM MENINGKATKAN PEREKONOMIAN MASYARAKAT DI DESA BARANIA KECAMATAN SINJAI BARAT - Prabowo, Aswin; Fatmawati, Fatmawati; Mone, Ansyari (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
The purpose of this study was to determine the strategy of developing community-based tourism (community based tourism) in Kampung Galung. The type of research used is descriptive qualitative research, this type of research is descriptive. Data collection techniques used are interviews, documentation, and observation. Research informants are the government and the community. The results of this study indicate a community-based tourism development strategy (community based tourism) in the village of Galung, First, external management in involving the community in decision making. Second, the management of the Kampung Galung tourist attraction provides benefits from tourism. Third, involve managers, the government and the community regarding proper development procedures. Fourth, the government and managers always provide space for the community to maintain their culture.